Dynamic Analysis of Eccentrically Stiffened Sandwich Thick Plates with Auxetic Honeycomb Core and GPL-RC Face Layers under Blast Loading - Quang, Vu Dinh (VNU Journal of Science: Mathematics - Physics, 2021)
The object of this study is eccentrically stiffened sandwich thick plates with the core layer made of negative poisson material. The analytical method base on the first order shear deformation theory (FSDT) is applied to analyse dynamic response and vibration of the plates. The numerical results of the study have been compared with other studies to evaluate the reliability of the calculation. The analysis results of the nonlinear dynamic response and the vibration show that the elastic foundation and the graphene volume ratio positively impact the behavior of the plates. On the other hand, imperfection and thermal environment have a negative effect on the behavior of sandwich plates. Research has also been performed to evaluate the effect of blast load, axial load and shape on the dynamic response of the plate.